Spatial analysis of the effect of housing unit fragmentation on infrastructure services in the city of Baghdad: A comparative study between Al-Salam neighborhood and Al-Khadra neighborhood - Abdul-Jabbar, Zainab Abdul-Sattar; Hassan, Areej Bahjat Ahmed (Al-Adab Journal, 2022)
The city of Baghdad, including the neighborhoods of the study area, has suffered in recent years from many problems, and the reason is the unplanned increase in population numbers, weak laws, a decline in monitoring by municipal departments, and the division of housing units into units with smaller areas. One of these problems resulted from the problem of the housing deficit that A storm in our country, which is caused by the increase in population in cities compared to the lack of housing supply. Through a field study of two neighborhoods of the city of Baghdad, the first neighborhood, which is (Al-Salam neighborhood) is located within the Al-Shula municipality, which is considered one of the poor neighborhoods and is characterized by a high population number, as the number of residents in it reached (296,800) people in the year 2020 and is characterized by the small area of ​​housing units and the low economic level, Compared with the other neighborhood, which is (Al-Khadra neighborhood), which is located within Al-Mansour municipality and has a population of (68,824), and is characterized by a high economic level for its residents, with the availability of housing units with large areas. The study proved the existence and spread of the phenomenon of housing unit fragmentation in both the high-end and poor neighborhoods, but that its spread in the high-end neighborhoods (the green neighborhood) was a higher percentage and the percentage reached (70%), but in Al-Salam neighborhood the percentage reached (12%), and among the factors that helped The availability of large areas and wide facades, which helped to divide the original housing units into small parts, the area of ​​one part may reach only (50 m2). The results of the study showed that this phenomenon is constantly expanding and shed light on its negative effects that led to an increase in pressure on infrastructure services, which led to a deficit in many of these services. and recommendations for solving this problem.